Modulation Of Membrane Bound Atpases And Metabolizing Enzymes Against N-Nitosodiethylamine (Den) Induced Primary Liver Cancer In Wistar Albino Rats - K. LANGESWARAN,; A. J. JAGADEESAN,; M. P. BALASUBRAMANIAN, (International Journal of Pharma and Bio Sciences, 2012)
The present investigation was carried out to estimate the effect of bioactive compound limonin on various biological enzymes like Glycogen; Membrane bound ATPases, Carbohydrate metabolizing enzymes and Mitochondrial TCA cycle enzymes against N-nitrosodiethylamine (DEN) induced primary liver cancer in male Wistar albino rats. Liver cancer was induced by single intraperitonial injection of DEN (200 mg/kg). After 2 weeks of DEN administration, Phenobarbital (PB) was given to promote the cancer for up to 14 successive weeks. Limonin (50mg/kg/b.w/p.o) was given for 28 days to hepatocellular carcinoma bearing rats. After the experimental period, all the animals were sacrificed and serum and liver samples were collected for biochemical analysis. There was instability in the levels of biological enzymes when subjected to DEN induction. These altered enzyme levels were ameliorated significantly by administration of limonin at the concentration of 50mg/kg in drug-treated animals. This protective effect of limonin was associated with inhibition of LPO induced by DEN and to maintain these enzyme levels.